Answer:
i think i used it before
Step-by-step explanation:
Answer:
m∠H = 10°
Step-by-step explanation:
ΔFGH is an isosceles triangle. I made a diagram, so m∠F ≅ m∠H by B.A.T(base angle theorem). This is because an isosceles triangle have to congruent sides and angles.
Diagram is attached:
-Chetan K
Answer:
its 4
Step-by-step explanation:
1 2 3 4
hope i helped
Answer:
b = -1
Step-by-step explanation:
7(3b-1): 7 goes into the numbers by multiplying. This will give you 21b-7.
So now the equation should be like 21b-7=2b-26.
-7 and 2b swap places, making 21b-2b=7-26. It will give you 19b= -19.
Finally divide the two numbers (-19 / 19) and the solution will be b= -1.
If I didn't make a clear answer or a good explanation, please comment. I sometimes mess up my steps, and this is my first time using this.